Then Again, Maybe I Won't: A Novel - Blume, Judy. (Scarsdale, N.Y., : Bradbury Press, 1971)
Unable to accept or explain his family's newly acquired wealth, his growing interest in sex, and a friend's shoplifting habit, a thirteen-year-old finds the pains in his stomach getting worse and worse.
Keywords: Emotional problems -- Fiction